Evaluasi Kelayakan Implementasi Sistem Informasi Surveilans Kesehatan Ibu Anak dan Gizi dengan Model Task Technology Fit di Kabupaten Banyumas - Sri Bintang Pamungkas; Farid Agushybana; Kusworo Adi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
Banyumas Regency already has a supportive system in terms of maternal health and child health surveillance but has not been utilized optimally because it has not gone through a competent feasibility study, so the system cannot be applied according due needs. The purpose of this study is noticing at the feasibility study of the child maternal health surveillance system and nutrition in its application at Banyumas regency by using Task Technology Fit (TTF). Research is a quantitative study with a cross sectional approach. Respondents of this study were all coordinate midwives in the puskesmas in Banyumas regency which amounts totaling 39 people, according to the predetermined total sampling criteria. Data collection using a questionnaire method. Data analysis was performed using logistic regression. The results of the feasibility study of the maternal and child health health surveillance system in Banyumas District showed variables related to utilization including data suitability, system reliability, ease of use. The recommendation for the improvement of the feasibility study of maternal and child health health surveillance systems in Banyumas district is the improvement of infrastructure, as well as training and socialization.